Endobronchial ultrasound: launch of an ERS structured training programme. Issue 3 (September 2016) - Farr, Amy; Clementsen, Paul; Herth, Felix; Konge, Lars; Rohde, Gernot; Dowsland, Sarah; Schuhmann, Maren; Annema, Jouke
The systematic assessment of mediastinal anatomy and in particular lymph nodes gains increasing importance in malignant as well as in non-malignant diseases. However, the diagnosis and staging of lung cancer is the most frequent indication. Lung cancer is the fourth most prevalent form of cancer in Europe, with lung cancer making up the largest number of cancer-related deaths [1]. Between European countries there are variations in the incidence and mortality rates of lung cancer. These are reflected by differences in national health system policies, regional risk factors, disparities in human development and local cancer control measures [1]. International health systems are looking for more cost-effective and accurate tools for screening and diagnosing lung cancer and other respiratory diseases. ERS launches structured EBUS training programme http://ow.ly/br5P302vhh3